Maturation Along White Matter Tracts in Human Brain Using a Diffusion Tensor Surface Model Tract-Specific Analysis - Chen, Zhang; Zhang, Hui; Yushkevich, Paul A.; Liu, Min; Beaulieu, Christian (Frontiers in Neuroanatomy, 2016)
Previous diffusion tensor imaging (DTI) tractography studies have demonstrated exponential patterns of developmental changes for diffusion parameters such as fractional anisotropy (FA) and mean diffusivity (MD) averaged over all voxels in major white matter (WM) tracts of the human brain. However, this assumes that the entire tract is changing in unison, which may not be the case. In this study, a surface model based tract specific analysis was applied to a cross-sectional cohort of 178 healthy subjects (83 males/95 females) aged from 6 to 30 years to spatially characterize the age-related changes of FA and MD along the trajectory of 7 major WM tracts – corpus callosum and 6 bilateral tracts. There were unique patterns of regions that showed different exponential and linear rates of increasing FA or decreasing MD and peak maturation age along each tract. Faster FA-development rate was observed in genu of corpus callosum (CC) and frontal-parietal part of superior longitudinal fasciculus (SLF). Inferior corticospinal tract (CST), posterior regions of association tracts such as inferior longitudinal fasciculus, inferior frontal fasciculus and uncinate fasciculus also displayed an early developmental pattern for FA. MD decreases with age also exhibited this posterior-to-anterior WM maturation pattern for most tracts in females. Both males and females displayed similar maturation patterns along most large tracts; however, males had overall delayed maturation peaks compared with females in most tracts with the greater differences occurring in the CST and frontal-parietal part of SLF for MD. Therefore, brain white matter development has spatially-varying trajectories along tracts that depend on sex and the tract.